(untitled) (MAUSAM, 1971)
The variations of group velocities with period of the fundamental Rayleigh and Love waves along two profiles Kodaikanal (KOD)-New Delhi (NDI) and Kodaikanal (KOD)-Poona (POO) as well as along paths from few epicentres in the neighbourhood of New Delhi to KOD have been used to investigate the average crustmantle structure of Indian Peninsula. The periods range from 6 to 80 sec for Rayleigh waves and from 11 to 95 sec for Love waves. Theoretical dispersion curves for suitable models have been obtained to fit the observed data by using the group velocity perturbations for the variations of crust-mantle structural parameters. The structural models obtained show that the total crustal thickness is 41 km in the central part of the Peninsula and rises to 50 km in the Western Ghats region. The thickness of the granitic layer in these models is a bout 12 km. It has been observed that assumption of a simple isotropic mantle does not give a satisfactory fit to both Rayleigh and Love waves data at higher periods. A satisfactory fit has been obtained by considering the mantle to be anisotropic between the depths 50 and 140 km, where SH Velocity is higher than SV velocity.